THE EFFECTIVENESS OF NUTRITION EDUCATION THROUGH SOCIO-DRAMATIC METHOD TO VEGETABLE & FRUIT KNOWLEDGE AND CONSUMPTION IN 5-6 YEARS OLD CHILDREN - Luluk Hidayatul Maghfiroh; A Fahmy Arif Tsani; Fillah Fithra Dieny; Etisa Adi Murbawani; Rachma Purwanti (Media Gizi Indonesia, 2021)
Low consumption of vegetable and fruit in children was still commonly found. Appropriate and effective nutrition education methods are needed to increase knowledge and consumption of vegetable and fruit in children. This study aimed to know the effectiveness of nutrition education through socio-dramatic method of vegetable and fruit knowledge and consumption in children 5-6 years old.This study was a quasi-experiment with pre-test and post-test control group design. Research subjects were 36 Taman Putra Kindergarten children who were divided into treatment group who were given nutrition education with socio-dramatic method, and control group who were given nothing. The improvement of nutrition knowledge was assessed by pre-test and post-test with pictured form, while vegetable and fruit consumption were assessed by 3 Days Food Record instrument. A total of 15 subjects had low fruit vegetable knowledge, and more than 50% of subjects had less fi ber intake, types of vegetable consumption <7 types, the amount of vegetable intake <250 grams, and fruit <150 grams. The provision of nutritional education through sociodrama method was effective in increasing knowledge of fruit vegetables in pre-school children (p <0.001), as seen from the increase in average knowledge of treatment group compared to control group. But unfortunately, nutrition education through sociodrama method has not been able to signifi cantly increase fruit vegetable consumption in terms of both quantity and type (p> 0.05).